A role for the histone H2A deubiquitinase MYSM1 in maintenance of CD8+ T cells. Issue 1 (20th February 2017) - Förster, Michael; Boora, Rupinder K.; Petrov, Jessica C.; Fodil, Nassima; Albanese, Isabella; Kim, Jamie; Gros, Philippe; Nijnik, Anastasia
Summary: Several previous studies outlined the importance of the histone H2A deubiquitinase MYSM1 in the regulation of stem cell quiescence and haematopoiesis. In this study we investigated the role of MYSM1 in T‐cell development. Using mouse models that allow conditional Mysm1 ablation at late stages of thymic development, we found that MYSM1 is intricately involved in the maintenance, activation and survival of CD8 + T cells. Mysm1 ablation resulted in a twofold reduction in CD8 + T‐cell numbers, and also led to a hyperactivated CD8 + T‐cell state accompanied by impaired proliferation and increased pro‐inflammatory cytokine production after ex vivo stimulation. These phenotypes coincided with an increased apoptosis and preferential up‐regulation of p53 tumour suppressor protein in CD8 + T cells. Lastly, we examined a model of experimental cerebral malaria, in which pathology is critically dependent on CD8 + T cells. In the mice conditionally deleted for Mysm1 in the T‐cell compartment, CD8 + T‐cell numbers remained reduced following infection, both in the periphery and in the brain, and the mice displayed improved survival after parasite challenge. Collectively, our data identify MYSM1 as a novel factor for CD8 + T cells in the immune system, increasing our understanding of the role of histone H2A deubiquitinases in cytotoxic T‐cell biology. Abstract : The paper identifies MYSM1 as a novel factor involved in the maintenance, activation and survival of CD8 + T cells under homeostatic conditions as well as during the course of an infection, thereby increasing our understanding of the role of histone H2A deubiquitinase in cytotoxic T‐cell biology.